2020
DOI: 10.1029/2019ja027727
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Ionospheric Mass Source for Jupiter's Magnetosphere: An Ionospheric Outflow Model for the Auroral Regions

Abstract: Ionospheric outflow is the flow of plasma initiated by a loss of equilibrium along a magnetic field line, which induces an ambipolar electric field due to the separation of electrons and ions in a gravitational field and other mass‐dependent sources. We have developed an ionospheric outflow model using the transport equations to determine the number of particles that flow into the outer magnetosphere of Jupiter. The model ranges from 1,400 km in altitude above the 1 bar level to 2.5 RJ along the magnetic field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 37 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…While these beams are not likely the source of protons in the inner‐most portions of the magnetosphere, they may be an important contribution toward explaining observations of protons dominating the dawn‐side of the outer magnetosphere (McComas et al., 2017c) and far down the magnetotail (McComas et al., 2007, 2017b). If Jupiter is the primary source of magnetospheric protons in the inner magnetosphere (within ∼20 R J ), they are likely sourced at latitudes equatorward of the main emissions and at lower energies than 100 eV discussed in this work, which would also explain why these estimates are on the lower end of previous ionospheric mass fluxes (Nagy et al., 1986; Martin et al., 2020). The mass outflow found here of 1–5 kg s −1 is consistent with the values of 4.3–8.5 kg s −1 predicted to occur within a nominal 2° main oval (Martin et al., 2020).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…While these beams are not likely the source of protons in the inner‐most portions of the magnetosphere, they may be an important contribution toward explaining observations of protons dominating the dawn‐side of the outer magnetosphere (McComas et al., 2017c) and far down the magnetotail (McComas et al., 2007, 2017b). If Jupiter is the primary source of magnetospheric protons in the inner magnetosphere (within ∼20 R J ), they are likely sourced at latitudes equatorward of the main emissions and at lower energies than 100 eV discussed in this work, which would also explain why these estimates are on the lower end of previous ionospheric mass fluxes (Nagy et al., 1986; Martin et al., 2020). The mass outflow found here of 1–5 kg s −1 is consistent with the values of 4.3–8.5 kg s −1 predicted to occur within a nominal 2° main oval (Martin et al., 2020).…”
Section: Discussionmentioning
confidence: 67%
“…If Jupiter is the primary source of magnetospheric protons in the inner magnetosphere (within ∼20 R J ), they are likely sourced at latitudes equatorward of the main emissions and at lower energies than 100 eV discussed in this work, which would also explain why these estimates are on the lower end of previous ionospheric mass fluxes (Nagy et al, 1986;Martin et al, 2020). The mass outflow found here of 1-5 kg s -1 is consistent with the values of 4.3-8.5 kg s -1 predicted to occur within a nominal 2° main oval (Martin et al, 2020). While Juno has made direct observations of ionospheric H + at latitudes between the main emissions and Io's orbital footprint (Valek et al, 2019) and near the equator (Valek et al, 2020), thus far it has been difficult to constrain the ionospheric outflow rate in situ.…”
Section: Discussionmentioning
confidence: 80%
“…Previously, Martin et al. (2020), showed that at Jupiter the CF does not surpass the gravitational force until beyond two planetary radii owing to the the larger planetary mass. At Jupiter, considering the effects of FACs and CF on ionospheric outflow shows a 90% increase in total mass source rate (from 3.9 to 7.7 kg s −1 ), whereas in this study the inclusion of FACs and CF increase the total mass source from 3.2 to 17.7 kg s −1 , a 450% increase.…”
Section: Discussionmentioning
confidence: 98%
“…Martin et al. (2020) argued for the presence of an additional subauroral source region powered by radial currents in equatorial region of Jupiter's magnetosphere, based on the data found by Valek et al. (2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation